Pre-transplant type 2 diabetes mellitus is associated with higher graft failure and increased 5-year mortality after heart transplantation - Rivinius, Rasmus; Gralla, Carolin; Helmschrott, Matthias; Darche, Fabrice Fernand; Ehlermann, Philipp; Bruckner, Thomas; Sommer, Wiebke; Warnecke, Gregor; Kopf, Stefan; Szendrödi, Julia; Frey, Norbert; Kihm, Lars Philipp (Frontiers in Cardiovascular Medicine, 2022)
AimsCardiac transplant recipients often suffer from type 2 diabetes mellitus (T2DM) but its influence on graft failure and post-transplant mortality remains unknown. The aim of this study was to investigate the long-term effects of pre-transplant T2DM in patients after heart transplantation (HTX).MethodsThis study included a total of 376 adult patients who received HTX at Heidelberg Heart Center between 01/01/2000 and 01/10/2016. HTX recipients were stratified by diagnosis of T2DM at the time of HTX. Patients with T2DM were further subdivided by hemoglobin A1c (HbA1c ≥ 7.0%). Analysis included donor and recipient data, immunosuppressive drugs, concomitant medications, post-transplant mortality, and causes of death. Five-year post-transplant mortality was further assessed by multivariate analysis (Cox regression) and Kaplan-Meier estimator.ResultsAbout one-third of all HTX recipients had T2DM (121 of 376 [32.2%]). Patients with T2DM showed an increased 5-year post-transplant mortality (41.3% versus 29.8%; P = 0.027) and had a higher percentage of death due to graft failure (14.9% versus 7.8%; P = 0.035). Multivariate analysis showed T2DM (HR: 1.563; 95% CI: 1.053-2.319; P = 0.027) as an independent risk factor for 5-year mortality after HTX. Kaplan-Meier analysis showed a significantly better 5-year post-transplant survival of patients with T2DM and a HbA1c < 7.0% than patients with T2DM and a HbA1c ≥ 7.0% (68.7% versus 46.3%; P = 0.008) emphasizing the clinical relevance of a well-controlled T2DM in HTX recipients.ConclusionPre-transplant T2DM is associated with higher graft failure and increased 5-year mortality after HTX.
Gesehen am 29.07.2022